Substance-Treatment Professionals' Perceived Barriers to Incorporating Mindfulness Into Treatment. (5th December 2016) - Edwards, Emily Rachel; Cohen, Mia Gintoft; Wupperman, Peggilee
ABSTRACT: Background : Despite scientific favor, psychological interventions supported by research are often underutilized by practitioners due to perceived obstacles in implementation. Increased transparency between researchers and practitioners throughout treatment development and dissemination is therefore necessary. The rising popularity of mindfulness-based approaches in the treatment of substance-use disorders suggests such transparency is necessary in further developing, disseminating, and implementing such approaches within the context of substance treatment. Objectives : The present study aimed to increase transparency by surveying substance-treatment professionals regarding their perceptions of barriers to adopting mindfulness in the treatment of substance use. Methods : Substance-treatment professionals throughout the United States ( N = 103) completed an online survey about their perceptions of potential barriers to implementing mindfulness into substance treatment. Results : Overall, professionals were moderately familiar with mindfulness as a treatment for substance use. Approximately one-third reported providing mindfulness in substance treatment; however, only 7% reported providing mindfulness using a research-supported treatment manual. Across professionals of various backgrounds, the need for further training was rated as the greatest barrier to implementation. Conclusions/Importance : Results suggest that practitioners are generally familiar with and willing to implement mindfulness in the treatment of substance use. Future research and implementation efforts should focus on methods of increasing training availability, accessibility, and relevance to address the needs and expectations of substance-treatment professionals.